Marine Environmental Protection Under UNCLOS And Beyond: Analyzing Legal Gaps, Enforcement Challenges, And Emerging Global Frameworks - Akash Manwani; Dr. Sagar Kumar Jaiswal (Kurdish Studies, 2022)
The “United Nations Convention on the Law of the Sea” (UNCLOS) is a key legal framework governing maritime rights, with profound implications for environmental protection and sustainable management of marine resources. Established to address diverse oceanic issues, UNCLOS sets guidelines on territorial seas, exclusive economic zones, and navigation rights, while also enforcing regulations on pollution and resource exploitation. A cornerstone of environmental law, UNCLOS facilitates international cooperation, with the “International Maritime Organization” (IMO) and the “UN Environment Programme” (UNEP) playing essential roles in developing supplementary frameworks for pollution prevention and resource conservation. Additionally, the “Biodiversity Beyond National Jurisdiction” (BBNJ) treaty enhances marine biodiversity protection on the high seas, aligning with UNCLOS to promote ecosystem health. Challenges persist in areas such as flag state oversight, land-based pollution, and dispute resolution, yet UNCLOS’s adaptability enables diverse nations to balance economic, environmental, and security concerns. Through ongoing collaboration, nations are working toward a sustainable maritime future, addressing both established and emerging environmental threats.